Designing Vocabulary Learning Media Through Arts And Crafts For Primary School Teacher Training - Adetya Nor Rizkyka (Universitas Achmad Yani Banjarmasin, 2022)
Vocabulary in English is a common problem encountered in teaching and learning. This study aims to describe the steps of designing or developing vocabulary learning media using art and crafts. The purpose of this study is to teach primary school teacher training on the third-semester at Achmad Yani University Banjarmasin. This study used classroom action research. This method emphasizes on textbooks, journals and other relevant sources as sources of data and theoretical studies. The variables focused on here include the use of various art and craft activities in vocabulary teaching as independent and the success level of the students to present and participate in their learning English vocabulary.